Comparison of Rainfall Interpolation Methods in Langat River Basin - Hassim M.; Yuzir A.; Razali M.N.; Ros F.C.; Chow M.F.; Othman F. (Institute of Physics Publishing, 2023)
Disasters; Errors; Inverse problems; Mean square error; Rain; Rain gages; Rivers; Watersheds; Disaster mitigation; Hydrology modeling; Interpolation method; Inverse distance weighting; Rainfall interpolation; Root mean square errors; Spatial interpolation; Statistical evaluation; Interpolation